1999
DOI: 10.1007/bf02707388
|View full text |Cite
|
Sign up to set email alerts
|

Capital mobility and EU enlargement

Abstract: *The EU has recently entered accession talks with five transition economies of eastern Europe. Membership in the EU would require inter alia the full liberalization of capital flows. This paper provides empirical evidence on the openness towards foreign capital that the accession states have attained so far on the basis of the correlation between domestic saving and investment. A comparison with the southern members of the EU shows that the countries under review have reached a similar degree of integration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…These results confirm the hypotheses of Buch (1999) that the central and eastern European countries have already reached the same degree of integration into the world capital market like the EMU countries and that the accession process would likely not further increase the degree of capital mobility, since the CEEC-5 already have a higher degree of capital mobility than the EMU countries. That might be explained with efforts of the CEEC-5 not only to reduce barriers toward the European, but also toward the world capital market.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…These results confirm the hypotheses of Buch (1999) that the central and eastern European countries have already reached the same degree of integration into the world capital market like the EMU countries and that the accession process would likely not further increase the degree of capital mobility, since the CEEC-5 already have a higher degree of capital mobility than the EMU countries. That might be explained with efforts of the CEEC-5 not only to reduce barriers toward the European, but also toward the world capital market.…”
supporting
confidence: 85%
“…Taken this criticism into account and applying the FeldsteinHorioka test to other countries and periods however has not solved the FeldsteinHorioka paradox. Buch (1999) was the first that used the Feldstein-Horioka approach to measure the degree of international capital mobility in central and eastern European countries. In her seminal paper on capital mobility and EU enlargement, she estimated the degree of financial integration for a panel of central and eastern European countries (Czech Republic, Estonia, Hungary, Poland and Slovenia).…”
Section: Measuring Financial Market Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In both studies results were in favor of the higher degree of the capital mobility inside the EU than between OECD members. Buch (1999) for example, in her study on the transition economies of the EU, found evidence of a similar degree of capital mobility in the transition economies of the EU compared to that of OECD countries and that less developed transition members of the EU have a higher level of correlation between investment and savings than more advanced transition economies. Heterogeneity b etween samples of countries, considered periods and employed econometric techniques bring contradictory results which continue to span debates on FHP.…”
Section: Introductionmentioning
confidence: 97%